Prevalence of metabolic syndrome and its components based on International Diabetes Federation (IDF) definition in Yogyakarta Special Region, Indonesia - Choo Hao Jian; Fatwa Sari Tetra Dewi; Elizabeth Henny Herningtyas (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
ABSTRACTMetabolic syndrome (MetS) is a group of risk factors which increase morbidity and mortality for cardiovascular disease and diabetes. The prevalence of MetS has been on the rise. No previous study has described the prevalence of MetS in Yogyakarta Special Region and its components. The study aim was to determine the prevalence of MetS and it’s components in Yogyakarta Special Region, Indonesia. A total of 766 male and female subjects aged ≥40 were analyzed in this retrospective study based on secondary data from the Indonesian Family Life Survey batch 4 (IFLS 4). MetS was defined by International Diabetes Federation (IDF) criteria with ethnicity-specific values for waist circumference. Prevalence of MetS and characteristic of each component of MetS were expressed as mean or %. The difference of the MetS components was evaluated by t-test and chi-square. Prevalence of MetS in Yogyakarta Special Region was 13.19%. The most common of MetS component was hypertension (60.44%), followed by dyslipidemia (56.27%), central obesity (32.38%), pro-inflammatory state (15.71%) and insulin resistance (0.78%). There was a higher prevalence of MetS in females compared to males (15.88 vs 10.19%), pre-elderly compared to the elderly (13.90 vs 12.19%), Javanese compared to other ethnicities (13.23 vs 10.00%), and urban compared to rural populations (15.06 vs 8.37%). In conclusion,the prevalence of MetS in Yogyakarta Special Region is 13.19% with hypertension and dyslipidemia as the most common component.